Новітній український анекдот як виклик ХХІ століттю - Кімакович, І. (Народна творчість та етнографія, 2005)
This communication views folklore anecdote as an instrument of ideological influence on the mind of masses. Aesthetics and philosophy of the genre, its poetics and the ways of its existence in tradition have been analyzed.